2019
DOI: 10.1155/2019/9342792
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis of Suspected Myocarditis and Cardiomyopathy Associated with Viral Infection of the Myocardial Tissue: A Meta-Analysis of Cohort Studies

Abstract: Aim. Myocarditis and cardiomyopathy impose a substantial economic burden on society. Many studies have examined the effects of various predictors on the prognosis of these diseases, such as the left ventricular systolic function, the New York Heart Association glomerular filtration rate, the QT interval, and the presence of viruses. In the present study, we conducted a meta-analysis of cohort studies to investigate the significance of the presence of viruses in the myocardial tissue on the prognosis of these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
2
9
1
1
Order By: Relevance
“…The role of viral infection remains controversial. What is more, recently published metaanalysis of 10 studies (1006 patients with myocarditis or DCM) showed no significant difference in the prognosis of virus-positive and virus-negative patients [70]. However, in the setting of infective myocarditis, a targeted anti-viral therapy may be used, both in acute and chronic myocarditis.…”
Section: Anti-viral Therapymentioning
confidence: 99%
“…The role of viral infection remains controversial. What is more, recently published metaanalysis of 10 studies (1006 patients with myocarditis or DCM) showed no significant difference in the prognosis of virus-positive and virus-negative patients [70]. However, in the setting of infective myocarditis, a targeted anti-viral therapy may be used, both in acute and chronic myocarditis.…”
Section: Anti-viral Therapymentioning
confidence: 99%
“…However, histological examination, immunohistochemistry, and microbial genome and gene expression profiling are still valuable for diagnosis, follow-up, and prognosis. 30 …”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…It is important to note that the long-term cardiac implications of acute myocardial injury, especially when incurred at a young age, are not well known. A meta-analysis of cohort studies of suspected myocarditis in the presence of both viral infection and virus-negative patients found no significant differences in prognosis in terms of all-cause death, heart transplant, or re-hospitalization due to fatal arrhythmia and heart failure [ 28 ]. Observational studies assessing myocardial injury following COVID-19 infections found that persistent inflammation and regional fibrosis are common findings in patients recovered from viral myocarditis, and is associated with adverse outcomes [ 29–34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing evidence for incomplete recovery from post-viral autoimmune dysfunction [ 1 , 28 , 36–39 ], the long-term sequelae of vaccine-driven myocarditis are less clear [ 14 , 26 , 40 , 41 ]. One study using large cohort data demonstrated that viral infection is associated with a much greater risk of myocarditis, as compared to vaccine-induced myocarditis [ 42 ].…”
Section: Introductionmentioning
confidence: 99%